TRANSFORMASI KEBIJAKAN PENDIDIKAN MELALUI KEPEMIMPINAN INKLUSIF DI SEKOLAH - Kusumo Dewi, Retno; Handoyo, Eko; Rokhman, Fathur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the transformation of educational policies through inclusive leadership at SMP Dorkas Lasem, a private junior high school in Rembang Regency with a highly diverse student population. The principal implements inclusive leadership to ensure that policies accommodate diversity in religion, ethnicity, economic background, and student interests. The study employs a qualitative descriptive approach, using interviews, observations, and documentation analysis to explore how inclusive leadership influences policy transformation. Findings indicate that several factors support the successful implementation of inclusive education policies, including the principal’s competence, teacher collaboration, and parental involvement. However, challenges such as differences in student and teacher backgrounds, parental understanding of inclusivity, and surrounding cultural influences persist. To address these challenges, the school employs strategies such as community learning groups, continuous monitoring, and collaboration with external parties. The study highlights the importance of inclusive leadership in creating a fair and sustainable education system, emphasizing the need for ongoing evaluation and stakeholder engagement.